Upaya Pencegahan Penyakit dengan Cuci Tangan Pakai Sabun (CTPS) pada Anak Melalui Bercerita menggunakan Boneka Tangan - Aprilia Nuryanti; Rahayu Setyaningsih (Abdimas Universal, 2023)
Clean and Healthy Living Behavior (PHBS) is said to be one of the main determinants of the health status of the community, including children in households and schools. Worms, diarrhea, skin disease, toothache, and malnutrition are the impacts of low PHBS. Hand washing is a simple habit but has a big impact on reducing morbidity. The purpose of the activity is to teach children about PHBS Washing Hands with Soap (CTPS). Counseling methods by telling stories using hand puppets and demonstrations. The activity targets are children aged 3 to 12 years and their accompanying parents. The number of child participants was 19 people with 10 accompanying parents. The observation results showed that all children participated in the activity from start to finish and most (57.9%) of the children were able to practice CTPS correctly. The educational method using storytelling with hand puppets and demonstrations is considered effective for conveying health education. This CTPS health education must be followed up by habituating children's behavior both at home, at school, or anywhere with parental assistance.